Delayed plant genetic responses to forest edge dynamics and their conservation implications - Lore Hostens; Christophe Metsu; Elissar Alam; Kasper Van Acker; Gerrit Peeters; Sander de Beer; Yannick Gansemans; Eugenija Kupcinskiene; Lina Jociene; Edvina Krokaite‐Kudakiene; Jolina Paulssen; Leonie Mazalla; et al. (Conservation Biology, 2026)
Understanding genetic responses to forest dynamics is essential for predicting the long‐term viability of understory plant populations and for developing effective conservation strategies. We investigated genetic extinction debt and colonization credit in broad‐leaved enchanter's nightshade ( Circaea lutetiana ), a clonal forest understory species, across its European range. Using pooled genotype‐by‐sequencing data from 40 forest edge and core populations, we examined to what extent population size, latitude, and historical changes in forest configuration may predict genetic diversity. Historical forest configuration profoundly shaped present‐day genetic diversity. Long‐established forest edge populations exhibited significantly reduced allelic richness (−9%) compared with core populations, indicating the partial payoff of a genetic extinction debt. In contrast, populations from recently established forest edges maintained allelic richness similar to core populations, suggesting delayed population genetic responses to land‐use changes. Finally, populations established in areas that were afforested during the past 250 years exhibited lower allelic richness (−10%) than historical forest core populations, indicating a delay in genetic recovery and thus a potential genetic colonization credit. Our results highlight that C. lutetiana populations are not at equilibrium with the current forest configuration, underscoring the role of lagged genetic responses across very long periods. Population size, and to a lesser extent connectivity, further mediated genetic diversity, with smaller, isolated populations being particularly vulnerable to genetic erosion. Given the limited research on delayed evolution in forest understory species, our results improve understanding of extinction risk dynamics and underscore the need for history‐informed restoration efforts.

Changes in How Climate Forces the Vegetation of Southern Africa - Steven I. Higgins; Timo Conradi; Shasank Ongole; Jane Turpie; Joshua Weiss; Urs Eggli; Jasper A. Slingsby (Ecosystems, 2023)
Global climatic changes are altering ecosystem structure and functioning, yet detecting and forecasting such change is difficult. In this study, we use the concept of a phytoclime—a region where climate favours the growth of similar combinations of plant types—to examine how changes in climate forcing may impact on regional vegetation. We use species distribution data to estimate the parameters of a physiological plant growth model for 5006 vascular plant species common to southern Africa. Plant type suitability surfaces are calculated as the average climatic suitability of locations for all species belonging to a plant type. We calculated plant type suitability surfaces for ten different plant types. The resulting surfaces were used to produce a spatial classification of phytoclimes, which we interpret as regions that can climatically support particular plant type combinations. We use the phytoclime definitions and climatologies from five global circulation models (GCMs) simulating three shared economic pathways (SSPs) to forecast how the climatic forcing underlying the phytoclimes will change. Our analyses forecast that change in phytoclime state will be widespread throughout the region. There were, however, substantial differences in the timing of when changes would occur. The central interior of the region was forecast to change earlier than the arid west and southern coast. These differences in timing were driven by differences in the responses of trees, succulents, C3 and C4 grasses to the GCMs forecast aridification of the region’s central interior. Phytoclime modelling provides an indication of the potential of a region’s climate to support different plant types; it thereby provides forecasts of the potential impacts of climate change on regional vegetation structure and functioning.

Biogeographic historical legacies in the net primary productivity of Northern Hemisphere forests - Timo Conradi; Koenraad Van Meerbeek; Alejandro Ordonez; Jens‐Christian Svenning (Ecology Letters, 2020)
It has been suggested that biogeographic historical legacies in plant diversity may influence ecosystem functioning. This is expected because of known diversity effects on ecosystem functions, and impacts of historical events such as past climatic changes on plant diversity. However, empirical evidence for a link between biogeographic history and present‐day ecosystem functioning is still limited. Here, we explored the relationships between Late‐Quaternary climate instability, species‐pool size, local species and functional diversity, and the net primary productivity (NPP) of Northern Hemisphere forests using structural equation modelling. Our study confirms that past climate instability has negative effects on plant functional diversity and through that on NPP, after controlling for present‐day climate, soil conditions, stand biomass and age. We conclude that global models of terrestrial plant productivity need to consider the biogeographical context to improve predictions of plant productivity and feedbacks with the climate system.

Species–area relationships in continuous vegetation: Evidence from Palaearctic grasslands - Jürgen Dengler; Thomas J. Matthews; Manuel J. Steinbauer; Sebastian Wolfrum; Steffen Boch; Alessandro Chiarucci; Timo Conradi; Iwona Dembicz; Corrado Marcenò; Itziar García‐Mijangos; Arkadiusz Nowak; David Storch; et al. (Journal of Biogeography, 2020)
Aim Species–area relationships (SARs) are fundamental scaling laws in ecology although their shape is still disputed. At larger areas, power laws best represent SARs. Yet, it remains unclear whether SARs follow other shapes at finer spatial grains in continuous vegetation. We asked which function describes SARs best at small grains and explored how sampling methodology or the environment influence SAR shape. Location Palaearctic grasslands and other non‐forested habitats. Taxa Vascular plants, bryophytes and lichens. Methods We used the GrassPlot database, containing standardized vegetation‐plot data from vascular plants, bryophytes and lichens spanning a wide range of grassland types throughout the Palaearctic and including 2,057 nested‐plot series with at least seven grain sizes ranging from 1 cm 2 to 1,024 m 2 . Using nonlinear regression, we assessed the appropriateness of different SAR functions (power, power quadratic, power breakpoint, logarithmic, Michaelis–Menten). Based on AICc, we tested whether the ranking of functions differed among taxonomic groups, methodological settings, biomes or vegetation types. Results The power function was the most suitable function across the studied taxonomic groups. The superiority of this function increased from lichens to bryophytes to vascular plants to all three taxonomic groups together. The sampling method was highly influential as rooted presence sampling decreased the performance of the power function. By contrast, biome and vegetation type had practically no influence on the superiority of the power law. Main conclusions We conclude that SARs of sessile organisms at smaller spatial grains are best approximated by a power function. This coincides with several other comprehensive studies of SARs at different grain sizes and for different taxa, thus supporting the general appropriateness of the power function for modelling species diversity over a wide range of grain sizes. The poor performance of the Michaelis–Menten function demonstrates that richness within plant communities generally does not approach any saturation, thus calling into question the concept of minimal area.

Woody encroachment in African savannas: Towards attribution to multiple drivers and a mechanistic model - Timo Conradi (Journal of Biogeography, 2018)